The Price-Setting Behavior of Austrian Firms: Some Survey Evidence - Josef Baumgartner; Claudia Kwapil; Johann Scharler (Oesterreichische Nationalbank (OeNB), 2005)
This paper explores the price-setting behavior of Austrian firms based on survey evidence. Our main result is that customer relationships are a major source of price stickiness in the Austrian economy. We also find that the majority of firms in our sample follows a timedependent pricing strategy. However, a substantial fraction of firms deviates from time-dependent pricing in the case of large shocks and switches to a state-dependent pricing strategy. In addition, we present evidence suggesting that the price response to various shocks is subject to asymmetries.
Keywords: C25; E30; 330; Price-setting behavior; Price rigidity